Mediators of the relationship between spiritual intelligence and social support on health behaviours of undergraduates in a public university in Malaysia - Omar Dev, Roxana Dev (2018)
The main purpose of the present study is to develop a health behaviour model by investigating the relationship of two psycho-social variables, spiritual intelligence and social support on selected mediators, emotional intelligence and self-efficacy towards health behaviour among undergraduates of Universiti Putra Malaysia. The investigated model is based on the Theory of Triadic Influence by Fly & Petraitis (1994). EI was seen as distal variable but in this study it is hypothesized as a distal-proximal variable. The study used a correlational research design. There were five instruments used for the study which were Health Behaviour Questionnaire (adapted from Bobroff, 2015), General Self-Efficacy Scale (Schwarzer & Jerusalem, 1993), Spiritual Intelligence Self-Report Inventory (King, 2008), Assessing Emotions Scale (Schutte, Malouff & Bhullar, 2009) and Interpersonal Support Evaluation List-College Version (Cohen, Mermelstein, Karmarck & Hoberman, 1985) which content validity were checked by a panel of experts. A pilot study was conducted on 50 UPM students to assess the reliability of the instruments. The value of Cronbach’s alpha was from .79 to .92. For the real data, proportionate stratified sampling technique was used with a sample size of 400 undergraduates who stayed in the dormitory at Universiti Putra Malaysia. The final coefficient ranges from .86 to .91. For data analysis, descriptive statistics (SPSS 21) and Structural Equation Modeling (AMOS 21) were used. The structural model of the study with 9 paths was tested and found fitting as per set criteria. Out of the 9 paths in the model, seven paths showed significant effects in the relationships explained by the model, while two paths did not. The paths that reflected significant relationship were as follows: 1) spiritual intelligence with health behaviour (β=.335, p<.001); 2) spiritual intelligence with emotional intelligence (β=.635, p<.001); 3) spiritual intelligence with self-efficacy (β=.285, p<.001); 4) social support with health behaviour (β=.128, p<.05); 5) social support with emotional intelligence (β=.098, p<.05); 6) emotional intelligence with self-efficacy (β=.225, p<.05); 7) self-efficacy with health behaviour (β=.300, p<.001). On the other hand, the paths that were not significantly related were relationship between social support and self-efficacy (β=.032, p>.05) and relationship between emotional intelligence and health behaviour (β=.107, p>.05). The results of the mediation tests indicated that self-efficacy partially mediated the relationship between spiritual intelligence and health behaviour. However, self-efficacy did not mediate the relationship of social and emotional intelligence on health behaviour. Besides that, emotional intelligence were seen to partially mediate the relationship between spiritual intelligence and self-efficacy Overall, the revised structural model of the study with 7 paths explained 40.7 % of emotional intelligence, 21.2 % of self- efficacy and 30.0% of health behaviour. This study has provided some new thoughts and insights on measuring self-efficacy based on students’ perceptions. Many researchers have identified self-efficacy as the most important predictor for health behaviour (Mathumardhi & Suparna, 2016; Jamshidi et al., 2018), however, high self-efficacy will be meaningless if there is no authentic way in addressing intrinsic aspects of life in terms of spirituality (Mathumardi & Suparna). Spiritual intelligence and self-efficacy hand in hand help university students to become useful members of the society, as in case individuals who care about promotive health behaviours. Hence more research should be done to validate this finding. Probable journey should incorporate a sequential exploratory design.